Prognostic implications of necroptosis-related long noncoding RNA signatures in muscle-invasive bladder cancer - Jiang, Kan; Wu, Lingyun; Yin, Xin; Tang, Qiuying; Yin, Jie; Zhou, Ziyang; Yu, Hao; Yan, Senxiang (Frontiers in Genetics, 2022)
Background: Bladder cancer (BLCA) is the sixth most common cancer in men with an increasing incidence of morbidity and mortality. Necroptosis is a kind of programmed cell death and plays a critical role in biological processes of bladder cancer (BLCA). However, current studies focusing on long noncoding RNA (lncRNA) and necroptosis in cancer are limited and there is no research about necroptosis-related lncRNAs (NRLs) in BLCA especially. Methods: We obtained the RNA-seq data and corresponding clinical information of BLCA from The Cancer Genome Atlas (TCGA) database. The 7 determined prognostic NLRs were analyzed by several methods and verified by RT-qPCR. Then, a risk signature was established based on the above prognostic NLRs. To identify it, we evaluate its prognostic value by Kaplan-Meier (K-M) survival curve and receiver operating characteristics (ROC) curve analysis. Moreover, the relationship between risk signature and clinical features, functional enrichment, immune landscape, and drug resistance were explored as well. Results: We constructed a signature based on 7 defined NLRs (HMGA2-AS1, LINC02489, ETV7-AS1, EMSLR, AC005954.1, STAG3L5P-PVRIG2P-PILRB, LINC02178). Patients in low-risk cohort had longer survival times than those in high-risk cohort and area under the ROC curve (AUC) value of risk signature was higher than other clinical variables. Functional analyses, the infiltrating level of immune cells and functions, ESTIMATE score, and immune checkpoint analysis all indicated that high-risk group was in a relative immune-activated state. In terms of treatments, patients in high-risk group were more sensitive to immunotherapy especially anti-PD1/PD-L1 immunotherapy and conventional chemotherapy. Conclusion: The novel NLR signature act as an invaluable tool for predicting prognosis, immune microenvironment, and drug resistance in muscle-invasive bladder cancer (MIBC) patients.